Design, construction and testing of an apricot tractor-trailed harvester - Torregrosa, A.; Chaparro, O.; Martín, B.; Ortiz, C.; Bernad, J. J.; Ortí, E.; Gil, J.; Pérez, M. (Spanish Journal of Agricultural Research, 2008)
The purpose of this research is to facilitate the mechanical harvesting of apricots (Prunus armeniaca L.) for industry. A tractor-trailed harvester was built to catch the fruits detached from apricot (cv. Búlida) trees by vibratory systems. This machine is a low profile catcher that can move under the trees in high-density canopies where umbrella-type harvesters cannot. The trailer is able to work under trees with as little free-trunk height as 0.35 m. The tests were donein 5- to 9-year-old apricot trees, planted in two frame, 2.5 m and 4.5 m in-the-row distances, with 6.5 m between rows in both cases. To detach the fruit, two hand-held pneumatic shakers were used. Harvest rate was 61 and 44 trees h-1 for each type of orchard, respectively. The main conclusion is that the trailer, together with branch-shakers, can work innarrow orchards of low canopy trees where other machines can not go in.